NEGARA DAN KEPEMIMPINAN DALAM PEMIKIRAN ALFARABI - Imam Sukardi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
The political concept of Alfarabi is derivated from the concept of Platonic, Aristotelian, and Islam. The ideal state is the state which is elaborated the universal values of humanism, not just limited to certain ethnic and nation which is emphasizing its obedience just to God, not the something else. In this paper, the writer tried to interpret the original works of Alfarabi which is directly related to his political thought and the other thinkers who are studying his political thought. In his political thought, Alfarabi emphasized that the main purpose of the state is to make the social-welfare for its citizens. Based on the organic theory, Alfarabi stated that the government of the state is just look-like the human organism system. In which, each of the existing element functioned to strengthen each other to achieve one goal. The ideal state for Alfarabi is the state which is having the goals for its citizen welfare, and who become the prime leader is a philosopher, who is having the prophetic character, having the wider knowledge, and able to communicate with al 'aql al fa’al trough al ‘aql mustafad.